2021
DOI: 10.1093/infdis/jiab170
|View full text |Cite
|
Sign up to set email alerts
|

Diminished Circulating Levels of Angiogenic Factors and Rage Ligands in Helminth–Diabetes Comorbidity and Reversal Following Anthelmintic Treatment

Abstract: Background Various epidemiological and experimental studies propose that helminths could play a preventive role against the progression of Type 2 diabetes mellitus (T2DM). T2DM induces microvascular and large vessel complications mediated by elevated levels of angiogenic factors and soluble RAGE ligands. However, the interactions between helminths and host angiogenic factors and RAGE ligands are unexplored. Methods To assess … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
0
7
1
Order By: Relevance
“…stercoralis infection ( Fig 3 ). These findings are contrary to previous work conducted in schistosomiasis [ 8 , 19 , 37 ], opisthorchiasis [ 47 ] and soil-transmitted helminths [ 48 ], which have all reported that infection with parasites could lead to changed serum lipid levels (LDL-C and/or HDL levels,) or BMI, which in turn helps to prevent the development of disease complications [ 21 , 49 ]. These differences might be a consequence of differing participant age groups, recently of infection, worm burdens, geographical area, culture, and dietary habits.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…stercoralis infection ( Fig 3 ). These findings are contrary to previous work conducted in schistosomiasis [ 8 , 19 , 37 ], opisthorchiasis [ 47 ] and soil-transmitted helminths [ 48 ], which have all reported that infection with parasites could lead to changed serum lipid levels (LDL-C and/or HDL levels,) or BMI, which in turn helps to prevent the development of disease complications [ 21 , 49 ]. These differences might be a consequence of differing participant age groups, recently of infection, worm burdens, geographical area, culture, and dietary habits.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent study has indicated that infection with S . stercoralis could play a beneficial role by limiting T2DM-related vascular complications [ 21 ]. However, the mechanism underlying the relationship between helminth infection, particularly S .…”
Section: Introductionmentioning
confidence: 99%
“…The baseline demographic characteristics and biochemical parameters have been described previously [ 5 8 , 13 ] and there were no significant differences in age, sex, BMI or other biochemical parameters between the 2 groups ( Table 1 ).…”
Section: Resultsmentioning
confidence: 87%
“…All recruited individuals were confirmed negative for other viral infections, as well as active and latent tuberculosis. This is the same cohort of individuals in our previously published reports [ 5 8 ].…”
Section: Methodsmentioning
confidence: 91%
See 1 more Smart Citation